30. EVALUATION OF ENDOSCOPIC SURGERY FOR SUTURING PERFORATED DUODENAL BULB ULCER AT E HOSPITAL FROM 1/2018 TO 12/2022 (Vietnam Journal of Community Medicine, 2024)
Objective: The aim of this study was to assess the outcomes of endoscopic surgery for suturingperforated duodenal bulb ulcers at E Hospital from January 2018 to December 2022.Research Method: A retrospective study was conducted on 122 patients with perforated duodenalbulb ulcers who underwent endoscopic suturing at the Department of Gastrointestinal Surgery andGeneral Surgery, E Hospital , from January 2018 to December 2022Results: All cases involved a single anterior duodenal bulb perforation. The success rate ofendoscopic suturing for duodenal bulb perforated ulcers was 121 out of 122 cases, with one caserequiring conversion to open surgery. The average surgical duration was 77.55 ± 28.5 minutes, andno intraoperative complications were recorded. Postoperative pain was low, as evidenced by theuse of pain medication for an average of 2.7 ± 1.8 days. The average time for resumption of bowelmovements was 3.42 ± 1.71 days. There were no cases of gastric output exceeding 500ml per day,and abdominal drainage was removed after 6.1 ± 2.5 days. 89.4% of patients had follow-upappointments scheduled for one year after surgery, and 12.3% experienced mild epigastricdiscomfort. Late complications included hypertrophic scars (2 cases), stenosis at the anastomoticsite (1 case), recurrent perforation (1 case), and recurrent ulceration at the suture site (5 cases).Conclusion: Endoscopic surgery for suturing perforated duodenal bulb ulcers offers severalbenefits for patients. It is associated with a shorter treatment duration, reduced postoperative pain,low complication rates, and low mortality rates.
Keywords: Perforated duodenal ulcer; Endoscopic surgery.